The Affects of Academic Controversy Method on Students’ Speaking Skills - siregar, delima megawati (The Explora, 2023)
This study aimed at investigating the effect of Structured Academic Controversy (SAC) on students speaking skill. Academic Controversy is a cooperative learning activity that leads students to argue different sides of an issue. Academic controversy is learning to take a position and defend it with reason is an essential skill in democratic society. The method involves a cooperative form of debate in which groups of four, divided into two groups, take turns representing two opposing views on an issue before attempting to reach a consensus on the issue. Students work in pairs to become familiar with one side of an issue, and then debate with another pair who has become familiar with the opposing side. Pairs then switch “sides,” become familiar with the opposing argument, and debate again. Finally, the two pairs come together to discuss the strengths and weakness of each side of the argument, come to a consensus about their collective opinion about the argument, and present that idea to the other quads. Finally, one other cooperative learning principle that can inform the use of Academic Controversy is ‘cooperation as a value’. Academic controversy method canimprove students’ speaking skill, by academic controversy, the students will be taught step by step to argue . The teacher can apply Academic controversy method to overcome the students’ speaking skill.